Mortality in type 1 diabetes diagnosed in childhood in Northern Ireland during 1989‐2012: A population‐based cohort study. Issue 1 (26th May 2017) - Morgan, Eileen; Black, Catherine R; Abid, Noina; Cardwell, Christopher R; McCance, David R; Patterson, Christopher C
Abstract : Objective: To investigate long‐term mortality rates and causes of death in individuals diagnosed with type 1 diabetes before the age of 15 years during the period 1989‐2012 or known to paediatric diabetes teams in 1989, in Northern Ireland. Methods: A cohort of 3129 patients from the Northern Ireland Childhood Diabetes Register was linked to death registrations and underlying causes, coded according to ICD‐9 or ICD‐10. Standardized mortality ratios (SMRs) were calculated as the ratio of observed to expected deaths by sex, attained age, time since diagnosis, calendar period, and cause of death. Results: Subjects were followed to December 31, 2012 giving 39 764 person‐years of follow‐up (median 12.1 years). In total, 59 subjects had died (1.5 per 1000 person‐years) compared with 19.9 deaths expected, an SMR of 296 (95% confidence interval (CI) 229‐382). Women had a significantly higher excess risk of mortality than men with SMRs of 535 (95% CI 361‐764) and 203 (95% CI 136‐291), respectively. Over half of the deaths (56%) were judged to be related or possibly related to diabetes with most of these due to acute ( n  = 24) or late ( n  = 6) complications. Conclusions: Subjects with type 1 diabetes diagnosed less than 15 years of age had 3 times the mortality risk of the general population. Over half of the deaths were related to acute or chronic complications of diabetes.